Direct evidence of the efficient hole collection process of the CoOx cocatalyst for photocatalytic reactions: a surface photovoltage study1. Issue 34 (14th September 2015) - Li, Shuo; Hou, LiBo; Zhang, Lijing; Chen, Liping; Lin, Yanhong; wang, Dejun; Xie, Tengfeng
<x xml:space="preserve">Abstract</x> The true effect of a cocatalyst on photocatalytic reactions is one of the major issues in photocatalysis research.